2016
DOI: 10.1128/jvi.00635-16
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of Interleukin-10 (IL-10) Signaling Pathways: Alternate Roles of Viral and Cellular IL-10 in Rhesus Cytomegalovirus Infection

Abstract: There is accumulating evidence that the viral interleukin-10 (vIL-10) ortholog of both human and rhesus cytomegalovirus (HCMV and RhCMV, respectively) suppresses the functionality of cell types that are critical to contain virus dissemination and help shape long-term immunity during the earliest virus-host interactions. In particular, exposure of macrophages, peripheral blood mononuclear cells, monocyte-derived dendritic cells, and plasmacytoid dendritic cells to vIL-10 suppresses multiple effector functions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 81 publications
0
16
0
Order By: Relevance
“…Both UCD52 and UCD59 are derived from serial propagation on primary monkey kidney epithelial cells, which express epithelial cell morphology and cell-specific markers [31] and contain a full-length UL128-UL131 coding capacity [32]. Previous studies have shown that inoculation of RhCMV-naïve rhesus macaques with UCD52 and UCD59 results in similar patterns of viremia and shedding in bodily fluids, comparable to those observed in colony-reared macaques naturally infected with circulating strains of endemic RhCMV [32][33][34]. On the other hand, CMV strain 180.92 was derived from serial propagation on rhesus fibroblasts, and is known to be a mixed virus with the dominant strain containing deletions in the UL/b' region while retaining an intact UL128-UL131 locus.…”
Section: Study Settingmentioning
confidence: 90%
See 1 more Smart Citation
“…Both UCD52 and UCD59 are derived from serial propagation on primary monkey kidney epithelial cells, which express epithelial cell morphology and cell-specific markers [31] and contain a full-length UL128-UL131 coding capacity [32]. Previous studies have shown that inoculation of RhCMV-naïve rhesus macaques with UCD52 and UCD59 results in similar patterns of viremia and shedding in bodily fluids, comparable to those observed in colony-reared macaques naturally infected with circulating strains of endemic RhCMV [32][33][34]. On the other hand, CMV strain 180.92 was derived from serial propagation on rhesus fibroblasts, and is known to be a mixed virus with the dominant strain containing deletions in the UL/b' region while retaining an intact UL128-UL131 locus.…”
Section: Study Settingmentioning
confidence: 90%
“…Because of this, it is likely that UCD52 has higher viral fitness in vivo, relative to both UCD59 and 180.92. The reason for UCD52 dominance over UCD59 is unknown: RhCMVnaïve macaques inoculated with UCD52 and UCD59 have similar patterns of viremia and shedding in bodily fluids [32][33][34]. That strain 180.92 did not become dominant is not surprising given previous findings of only low-level viral shedding and limited tissue dissemination of this strain in inoculated RhCMV-naïve macaques [35].…”
Section: Maternal Viral Load Dynamics Congenital Transmission and Smentioning
confidence: 96%
“…Interleukin-10 (IL-10), originally identified as an inhibitor of interferon-gamma (IFN-γ) and Interleukin-2 synthesis in Th2 cells [7], efficiently inhibits proliferative and cytokine responses in T cells and has shown to mediate both immunological unresponsiveness and the suppression of immune reactions [8,9]. As a key regulatory anti-inflammatory cytokine of multiple immune cells, IL-10 plays a pivotal role in limiting excessive inflammatory responses [10]. In the context of infectious disease, studies have reported an increase in pathogen clearance in the absence of IL-10 [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Typhimurium to cause systemic infection was described in mice treated with a neutralizing antibody that blocks the function of IL-10 ( 24 ). Interestingly, studies assessing persistent pathogens, such as Leishmania major ( 25 ), human cytomegalovirus ( 26 ), or Mycobacterium tuberculosis ( 27 ), have demonstrated that the absence of IL-10 leads to a better clearance of these pathogens, with variable degrees of immunopathology.…”
Section: Introductionmentioning
confidence: 99%